Numerical Analysis and Improvement of the Heat Exchanger Designed for Co-Generating Units - Ismail F.B.; Ali M.; Simic M.; Teoa S.S. (Elsevier B.V., 2023)
Computational efficiency; Computational fluid dynamics; Coolants; Efficiency; Flow of fluids; Fluid dynamics; Heat transfer; Knowledge based systems; Numerical analysis; Basic parameters; Coolant tubes; Design improvements; Different sizes; Generating unit; Heat transfer performance; Inlet velocity; System efficiency; Heat exchangers